Factors that Affect the Productivity of Palm Oil Plantations Self-Help Patterns in Jambi Province - Saidin Nainggolan; Mirawati Yanita; Manuel Leonardo (Randwick International of Social Science Journal, 2021)
This study aims to analyze factors that affect the productivity of oil palm plantations in Jambi Province. This research was conducted in sentra palm oil production in Merangin Regency with the research locus of South Veil Subdistrict selected purposive. The data used consists of Primary Data that includes social factors, economic factors, behavior of the use of production inputs and productivity of oil palm plantations.. The sample size is 80 farmers. Sample withdrawal by Simple Random Sampling method Restoration of structural models factors that affect the productivity of oil palm plantations is used sem Partial Least Squaremodel. The results showed that social factors, economic factors and institutional access factors were in the moderate category. The productivity of oil palm plantations is relatively low. Manifest social factors, which have a very real effect is the age of farmers. Manifest market access and product prices have a very real effect on economic factors. Manifest access to fertilizer procurement and fertilizer prices has a very real effect on the behavior of the use of production inputs and moderation variables that have a significant effect on the productivity of oil palm plantations. Policies that need to be done to improve. Is the strengthening of economic factors in the field of product prices and market access, and upay6a strengthening the behavior of farmers in the use of production inputs, especially fertilizers by providing subsidy incentives.